Implementasi Kartu Pola dalam Pembelajaran PBL untuk Meningkatkan Berpikir Kritis Matematika Kelas 2 SD - Siti Rukayah; Siti Inganah (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study explores the implementation of pattern cards in Problem-Based Learning (PBL) to enhance critical mathematical thinking in second-grade elementary students. The background highlights the need for effective teaching strategies that foster active learning and higher-order thinking skills in early mathematics education. The objective is to examine how using pattern cards within the PBL framework can improve students' ability to analyze and solve mathematical problems involving patterns. The method involves classroom implementation with observation and assessment of students' critical thinking progress during learning activities. Findings indicate that integrating pattern cards in PBL significantly improves students’ engagement and critical thinking skills in mathematics. This approach encourages students to explore patterns actively, reason logically, and collaborate in problem-solving tasks. The study implies that using concrete, interactive media such as pattern cards within PBL can be an effective strategy to develop critical mathematical thinking in young learners, offering valuable insights for educators aiming to enhance mathematics learning outcomes at the elementary level.